1984
DOI: 10.1002/jnr.490120107
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition of submandibular gland nerve growth factor (SMG‐NGF) responsiveness to thyroxine administration in neonatal mice

Abstract: The growth of the submandibular gland (SMG) was studied in newborn mice from birth to 15 days of age. Progressive changes in wet weight were observed to accompany changes in biochemical constituents such as RNA, protein, and lipid. Thyroxine (T4) administration from days 0-6 produced changes in SMG growth and SMG accumulation of RNA, protein, and lipid components relative to control pups treated with a similar volume of vehicle. This hormone regimen produced no measurable changes in SMG nerve growth factor (SM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
6
2

Year Published

1986
1986
1994
1994

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 23 publications
(6 reference statements)
1
6
2
Order By: Relevance
“…Moreover, the results suggest that exposure to thyroid hormones prior to 7 days of age is not necessary for induction of accelerated maturation of the SMG using EGF or NGF as the end-point determinant of such maturation. These results, however, differ slightly from those reported by Lakshmanan et al (25) who showed a significant increase in SMG EGF content in 15-day-old mice treated from birth compared to mice treated from day 7. The differences are difficult to reconcile since Lakshmanan et al (25) used essentially the same protocol employed in the present study.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Moreover, the results suggest that exposure to thyroid hormones prior to 7 days of age is not necessary for induction of accelerated maturation of the SMG using EGF or NGF as the end-point determinant of such maturation. These results, however, differ slightly from those reported by Lakshmanan et al (25) who showed a significant increase in SMG EGF content in 15-day-old mice treated from birth compared to mice treated from day 7. The differences are difficult to reconcile since Lakshmanan et al (25) used essentially the same protocol employed in the present study.…”
Section: Discussioncontrasting
confidence: 99%
“…These results, however, differ slightly from those reported by Lakshmanan et al (25) who showed a significant increase in SMG EGF content in 15-day-old mice treated from birth compared to mice treated from day 7. The differences are difficult to reconcile since Lakshmanan et al (25) used essentially the same protocol employed in the present study.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…7-15 days of age. Previous studies in this laboratory have indicated that both SMG-NGF and EGF acquire T4 responsiveness during the 2nd wk of life (17,18). Early actions of T4 on SMG include cytodifferentiation and organization (30).…”
Section: Discussionmentioning
confidence: 88%
“…Moreover, little information is available regarding the role of the autonomic nervous system in the growth and maturation of developing SMG (15,16). Recent studies in our laboratory have indicated that both SMG-NGF (17) and EGF (18) are T4 responsive during the second week of life. In view of the fact that T4 in newborn animals has profound effects on the developing nervous system (19,20), we examined the role of the SNS in mediating the T4 effect on developing SMG.…”
mentioning
confidence: 99%